A qualitative exploration of online forums to support resilience of rural young people in Australia - Carlisle, Karen; Kamstra, Peter; Carlisle, Emily; McCosker, Anthony; De Cotta, Tracy; Kilpatrick, Sue; Steiner, Artur; Kahl, Bianca; Farmer, Jane (Frontiers in Public Health, 2024)
Introduction: Prevention and early intervention are crucial strategies for improving young people's mental health and well-being. Building resilience is a key component of these strategies, especially among young individuals in rural areas who face well-documented mental health disparities. This study aimed to investigate how online mental health forums can contribute to enhancing individual resilience in young rural users.Methods: A sample of forum posts (n=1000) made by Australian rural users (18-25 years) on an online peer support mental health forum were qualitatively analysed. The analysis was guided by themes derived from the literature on indicators of rural resilience.Results: Analysis of forum posts showed evidence of rural resilience in forum users. Online peer support forums offered a virtual space for individuals to establish social connections, experience a sense of belonging, share information, acquire knowledge, and offer mutual support. There were indications of increased self-efficacy among forum users, as they demonstrated their ability to implement strategies for better managing their mental health.Discussion: These findings significantly contribute to our understanding of how online forums can enhance resilience factors that are beneficial for young people living in rural communities. In the context of prevention and early intervention, this study illustrates the intricate connections between forum design and user activity with resilience outcomes, providing valuable insights into the underlying causal mechanisms. Consequently, it emphasizes the importance of incorporating such digital interventions as integral components of mental health service ecosystems.